2019
DOI: 10.3390/nu11122844
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Grape Seed Proanthocyanidin Extract on Vascular Endothelial Function in Participants with Prehypertension: A Randomized, Double-Blind, Placebo-Controlled Study

Abstract: This study aimed to investigate the effects of grape seed proanthocyanidin extract (GSPE) on blood pressure and vascular endothelial function in middle-aged Japanese adults with prehypertension. We conducted a randomized, double-blind, placebo-controlled study on 6 men and 24 women aged 40–64 years old. The participants were randomized to receive tablets containing either low-dose (200 mg/day) or high-dose (400 mg/day) GSPE, or placebo, for 12 weeks. Systolic and diastolic blood pressures (SBP and DBP, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 65 publications
0
43
0
Order By: Relevance
“…The high antimicrobial and immunomodulatory activities of proanthocyanidins make them an interesting class of phytonutrients for the prevention and treatment of periodontal diseases [ 7 , 8 ]. An additional benefit is their natural dentin cross-linker activity and inhibition of MMPs, which may be helpful in adhesive dentistry [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The high antimicrobial and immunomodulatory activities of proanthocyanidins make them an interesting class of phytonutrients for the prevention and treatment of periodontal diseases [ 7 , 8 ]. An additional benefit is their natural dentin cross-linker activity and inhibition of MMPs, which may be helpful in adhesive dentistry [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The change in diastolic blood pressure (DBP) from baseline to 8 weeks was significantly higher in the low-dose and high-dose groups than in the placebo group ( p < 0.05) [ 17 ]. Additionally, Odai et al showed in a randomized, double-blind study of 21 non-smoking middle-aged women (including men), the oral intake of grape seed proanthocyanidins significantly reduced the mean systolic blood pressure (SBP) and DBP by 13.1 and 6.5 mmHg, respectively, in the high-dose (400 mg proanthocyanidin per day) group after 12 weeks of intervention [ 24 ]. A cohort study reported the anti-hypertensive effect of proanthocyanidins on middle-aged and elderly women.…”
Section: Resultsmentioning
confidence: 99%
“…Two clinical trials have already shown the potential for supplementation with GSEP to reduce blood pressure in non-pregnant patients with pre-hypertension ( Park et al, 2016 ; Odai et al, 2019 ). In addition, a previous preclinical study investigated the effect of intragastric administration of GSEP in pregnancy, using the L-NAME-induced hypertensive mouse model.…”
Section: Discussionmentioning
confidence: 99%